Las "Señoritas de Aras", un elemento geomorfológico amenazado (provincia de Huesca, España) - Pellicer Corellano, Franciso; Cancer Pomar, Luis; Echeverría Arnedo, María Teresa (Geographicalia, 2017)
A the built of a power-station in the Aras Valley, a tributary of Gallego river, will destroy a unique morphological element: the "Señoritas de Aras". The "dames Coiffées" landscape in an important geomorphological example, and the knowledge of its genesis and evolution serves as an educative exercise useful to get a good valoration of the natural environment and to evaluate the anthropic impacts.